Translating new evidence into clinical practice: a quasi-experimental controlled before–after study evaluating the effect of a novel outreach mentoring approach on knowledge, attitudes and confidence of health workers providing HIV and infant feeding counselling in South Africa. Issue 10 (27th October 2020) - Goga, Ameena; Doherty, Tanya; Manda, Samuel; Nkwenika, Tshifhiwa; Haskins, Lyn; John, Vaughn; Engebretsen, Ingunn M S; Feucht, Ute; Dhansay, Ali; Rollins, Nigel; Kroon, Max; Sanders, David; et al.
Abstract : Objectives: We report the effectiveness of a mentoring approach to improve health workers' (HWs') knowledge, attitudes and confidence with counselling on HIV and infant feeding. Design: Quasi-experimental controlled before–after study. Setting: Randomly selected primary healthcare clinics (n=24 intervention, n=12 comparison); two districts, South Africa. Participants: All HWs providing infant feeding counselling in selected facilities were invited. Interventions: Three 1–2 hours, on-site workshops over 3–6 weeks. Primary outcome measures: Knowledge (22 binary questions), attitude (21 questions—5-point Likert Scale) and confidence (19 questions—3-point Likert Scale). Individual item responses were added within each of the attitude and confidence domains. The respective sums were taken to be the domain composite index and used as a dependent variable to evaluate intervention effect. Linear regression models were used to estimate the mean score difference between intervention and comparison groups postintervention, adjusting for the mean score difference between them at baseline. Analyses were adjusted for participant baseline characteristics and clustering at health facility level. Results: In intervention and comparison sites, respectively: 289 and 131 baseline and 253 and 114 follow-up interviews were conducted (August–December 2017). At baseline there was no difference in mean number of correctly answered knowledge questions; this differed significantly at follow-up (15.2 in comparison; 17.2 in intervention sites (p<0.001)). At follow-up, the mean attitude and confidence scores towards breast feeding were better in intervention versus comparison sites (p<0.001 and p=0.05, respectively). Controlling for confounders, interactions between time and intervention group and preintervention values, the attitude score was 5.1 points significantly higher in intervention versus comparison groups. Conclusion: A participatory, low-intensity on-site mentoring approach to disseminating updated infant feeding guidelines improved HWs' knowledge, attitudes and confidence more than standard dissemination via a circular. Further research is required to evaluate the effectiveness, feasibility and sustainability of this approach at scale.